Protection for Victims of Domestic Violence Perpetrated by Military Members - Dharmaputra, Rio Perdana; Prastopo, Prastopo; Prasetyo, Boedi (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
This study examines the protection of Domestic Violence (KDRT) victims perpetrated by military personnel in Indonesia. Domestic violence cases involving military members are complex issues requiring serious attention, as they encompass aspects of general criminal law and military disciplinary law. Based on Law No. 23 of 2004 on the Elimination of Domestic Violence and Law No. 25 of 2014 on Military Discipline, military personnel who commit domestic violence can be subjected to both criminal and disciplinary sanctions. The legal process for military domestic violence cases involves two pathways: the criminal pathway, managed by the police and prosecution, and the military disciplinary pathway, handled by the authorized superior. Besides law enforcement, this study highlights the importance of protecting victims’ rights, such as security, physical and psychological recovery, and legal support. However, there are several obstacles to victim protection, including the strong patriarchal culture, lack of understanding about domestic violence within the military, and the complexity of the legal enforcement process. This study recommends increasing awareness of domestic violence, strengthening support for victims, and improving legal procedures to make the protection of domestic violence victims more effective.